“Crise dos braços”: escravidão, economia e imigração em Alagoas (1850-1888) - Araújo, Maria Valéria da Silva (2020)
The Eusébio Queiroz law, which established the end of the slave trade in 1850, initiated a process that determined the progressive reduction of slave workers in the province of Alagoas. In addition, the sugar crisis, slave escape and cholera were part of the region's scenario during the second half of the 19th century. The political elite and agrarian as worrying for the development of the crop pointed out these and other factors. According to this group, these conditions led to a workers' crisis. To reverse this situation, the search for immigrants was the option chosen by the provincial administration, especially in the final decade of slavery. The goal was to meet the need for labor in agricultural labor by bringing in immigrants, as there was a devaluation of the free national worker who was labeled as lazy and unable to obey the rules of formal labor. Therefore, the research proposed here intends to understand how Alagoas proceeded in view of this conjuncture.